2004
DOI: 10.1177/0748730403262870
|View full text |Cite
|
Sign up to set email alerts
|

Dec1 and Dec2 Expression is Disrupted in the Suprachiasmatic Nuclei of Clock Mutant Mice

Abstract: DEC1 and DEC2 are basic helix-loop-helix transcription factors that functionally resemble negative feedback components of the mammalian circadian clock. The genes Dec1 and Dec2 are expressed rhythmically in the rat suprachiasmatic nuclei, and Dec1 expression is stimulated by light in a time-dependent manner with the kinetics of an immediate early gene. DEC1 and DEC2 can inhibit CLOCK:BMAL1 transactivation of the clock gene Per1, suggesting that these transcription factors may help regulate circadian timing. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
21
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 28 publications
5
21
1
1
Order By: Relevance
“…Previously, we reported high expression levels of Dec1 and Per1 at ZT 2, soon after lights-on, in the extra SCN brain tissues (Butler et al, 2004). In the present experiment, we also observed increased gene expression, which suggested the positive masking of light (Dec1 and Dec2 in the liver and kidney).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Previously, we reported high expression levels of Dec1 and Per1 at ZT 2, soon after lights-on, in the extra SCN brain tissues (Butler et al, 2004). In the present experiment, we also observed increased gene expression, which suggested the positive masking of light (Dec1 and Dec2 in the liver and kidney).…”
Section: Discussionsupporting
confidence: 79%
“…Mutant CLOCK protein lacks 51-amino acids because of the deletion of exon 19 and becomes inactive (Gekakis et al, 1998;King et al, 1997). The expression profiles of all clock genes are disrupted with reduced peak expression in the SCN of Clock/Clock mice Kume et al, 1999;Oishi et al, 2000), and we recently reported that the expression of Dec1 and Dec2 in the SCN is also disrupted (Butler et al, 2004). These findings suggest that CLOCK activates Dec1 and Dec2 transcription in vivo.…”
mentioning
confidence: 90%
“…and rhythmic expression of Dec2 in the kidney of rats under a normal LD cycle. This differs not only from the circadian expression of Dec1 and Dec2 in the heart (present study) and in the SCN (Butler et al, 2004;Honma et al, 2002) and other peripheral tissues (Kawamoto et al, 2006;Kawamoto et al, 2004;Wu et al, 2008a;Wu et al, 2008b) of rats and mice but also from observations in mouse kidney (Hamaguchi et al, 2004;Noshiro et al, 2005), which suggests tissue-and species-specific mechanisms underlying the circadian expression of these two clock genes. This unusual phenomenon may be the cause of overlapping functions of Dec1 and Dec2 in maintaining and entraining circadian rhythms.…”
Section: Discussioncontrasting
confidence: 48%
“…Among suppressive factors for E boxes, DEC1 and DEC2 can bind directly to E boxes through their basic helix-loop-helix DNA binding domains (18,26), although it remains unclear whether DEC1 and DEC2 also bind to the EЈ boxes. In contrast, PER and CRY interact with the CLOCK/BMAL1 heterodimer but cannot bind directly to E/EЈ boxes, since they have no DNA binding domain.Dec1 expression shows robust circadian rhythms in the suprachiasmatic nucleus and various peripheral tissues (7,10,14,17,18,23), and it is further enhanced by light pulse, hypoxia, or growth factors, with the Dec1 level gradually increasing during chondrogenic or osteogenic differentiation (6,14,15,22,25,(27)(28)(29). Dec1 expression can also be elevated in various tissues by refeeding after starvation (17).…”
mentioning
confidence: 99%